Analysis and interpretation of the structural behaviour of Alqueva dam during the first filling of the reservoir - Tavares de Castro, A. (2011)
This paper presents the most relevant monitoring data and the interpretation of the structural behaviour of Alqueva dam during the first filling of the reservoir, which took place between February 2002 and January 2010. The safety control and the interpretation of the dam’s behaviour make use of the data provided by the monitoring system. In particular, the interpretation of the structural behaviour is based on: planimetric (radial and tangential) displacements, measured through plumb-line and geodetic methods; vertical displacements, measured with rod extensometers and obtained through geometric levellings; and temperatures, strains and stresses within the dam’s body, measured with embedded electrical resistance devices. A three-dimensional finite element model, considering the concrete viscoelastic behaviour and foundation specific characteristics, such as fault 22 located in the left bank, was developed for the numerical simulation of the dam structural behaviour. The time histories of the hydrostatic load and of the measured temperature within the dam’s body were considered in the model. The dam’s full-mixed concrete delayed behaviour was assumed to be represented by the Bažant and Panula’s basic creep function, evaluated from both in situ and laboratory tests. The results of a quantitative interpretation of the monitored displacements during this period, using a viscoelastic formulation, are close to those provided by the structural analysis.